2022
DOI: 10.1016/j.esxm.2022.100561
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Effects of two Pelvic Floor Muscle Treatments on Quality of Life and Sexual Function in Female Patients With Urinary Incontinence

Abstract: Background Adjuncts used clinically to improve the efficacy of Pelvic floor muscle training (PFMT) include electromyographic biofeedback (EB) and electrical stimulation (ES). Aim The purpose of this study was to investigate the effects of PFMT on patients' quality of life and sexual function in UI treatment. Different PFMT with different EB + ES treatments were designed in this study. In order to distinguish between 10 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Excessive activity of the detrusor muscle is a pathological-physiological cause of urinary incontinence that can be corrected by PFMT. Wang et al found that pelvic floor muscle contractions effectively inhibit detrusor muscle hypertrophy, increasing mechanical pressure on the urethra and preventing urinary incontinence ( 24 ). However, this does not seem to be widely supported, and the effectiveness of PFMT in treating post-RP urinary incontinence remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activity of the detrusor muscle is a pathological-physiological cause of urinary incontinence that can be corrected by PFMT. Wang et al found that pelvic floor muscle contractions effectively inhibit detrusor muscle hypertrophy, increasing mechanical pressure on the urethra and preventing urinary incontinence ( 24 ). However, this does not seem to be widely supported, and the effectiveness of PFMT in treating post-RP urinary incontinence remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%